Simple synthesis and surface facet-tuning of ultrathin alloy-shells of Au@AuPd nanoparticles via silver-assisted co-reduction onto facet-controlled Au nanoparticles. Issue 17 (13th April 2018) - Bi, Cuixia; Song, Yahui; He, Hongpeng; Wu, Chenshuo; Du, Wei; Huang, Lihui; Moehwald, Helmuth; Xia, Haibing
Abstract : The presence of silver on the surfaces of preformed Au nanoparticles is the key for the formation of ultrathin AuPd alloy-shells. Abstract : In this work, we report the synthesis of hexoctahedral (HOH-shaped), elongated tetrahexahedral (ETHH-shaped) and octahedral (OCT-shaped) Au@AuPd nanoparticles (NPs) via co-reduction of a trace amount of Au and Pd precursors by ascorbic acid (AA) with the aid of an elemental silver reservoir on the surface of the corresponding preformed Au NPs enclosed by different facets. Consequently, surface facets of alloy-shells of the resulting Au@AuPd NPs can be tuned, as they can retain the original surface facets of pre-formed, facet-controlled Au cores. It is found that both mass activities and specific activities of the three types of Au@AuPd NPs exhibit "volcano-type" dependence with respect to their Pd content in the surface of ultrathin AuPd alloy-shells. Moreover, HOH-shaped Au@Au0.20 Pd2.0 NPs simultaneously display the best activity and excellent stability due to the exposed high-index facets of the AuPd alloy-shell and the appropriate area ratio of active facets and inactive facets on the surfaces of ultrathin alloy-shells. Furthermore, their ECSA value, mass activity and specific activity are 125.8 m 2 g −1, 11.9 A mgPd −1 and 9.5 mA cm −2, respectively, which are about 4-fold, 31-fold, and 7-fold better than those (28.4 m 2 g −1, 0.38 A mgPd −1, and 1.34 mA cm −2 ) of commercial Pd/C catalysts, respectively. Thus, this work not only demonstrates that surface facets of core–shell Au@AuPd NPs can be engineered via co-reduction of a trace amount of Au and Pd precursors by AA with the aid of an elemental silver reservoir on the surface of preformed Au NPs, but also will open a new way to improve the electrocatalytic performance of CS Au@AuPd NPs by surface engineering.